Typology and Factorial Conditioning of Suicidal Behavior of Adolescents - Bonkalo, Tatyana I. (2021)
The problem of suicidal behavior of an individual continues to remain relevant, due to the increase in the number of suicides among people of different ages, on the one hand, and insufficient information about the factors of suicidal behavior of an individual. The purpose of the study is to identify the factors that determine the formation of a certain type of personality who committed suicidal attempts in adolescence. In order to identify the types of adolescent suicides, there was conducted a survey of 20 doctors in psychiatric clinical hospitals in Moscow. The survey results were processed using cluster analysis. To identify the factorial conditioning of suicidal behavior of each personality type, a complex of psychodiagnostic techniques was used, focused on the study of the characteristics of the emotional, value-semantic and behavioral spheres of the personality. The obtained empirical data were processed with the help of factor analysis. Three clusters have been identified that combine similar personality characteristics of suicides. It was specified that among adolescents there are the following personality types: “militant” (22%), “sacrifice” (54%) and “self-deprecating” (24%). Each type of adolescent suicide is due to the characteristics of the emotional, value-semantic and behavioral spheres of their personality. To develop targeted programs for the prevention of suicidal behavior among adolescents, it is necessary to take into account the results of the study, since such programs should be aimed at blocking the factors that form a certain type of suicide.